2009
DOI: 10.1111/j.1752-1688.2009.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Tributary Plunging in an Urban Lake (Onondaga Lake): Drivers, Signatures, and Implications1

Abstract: A combination of long‐term fixed‐frequency and robotic monitoring information for a polluted urban lake, Onondaga Lake, New York, and two of its tributaries is used to resolve the propensity for, and occurrences of, tributary plunging. Cooler temperatures (T) and higher salinity (S) are primarily responsible for the elevated density and plunging of one of these polluted streams for the summer through early fall interval. In‐lake transport of this plunging tributary, which receives inputs from combined sewer ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…The predicted inflow centroid depths in spring (Figure a) were deeper, when lake stratification was relatively weak. Moreover, the predicted centroid depth was somewhat deeper on these three days for Onondaga Creek compared to Ninemile Creek, consistent with the usually greater negative buoyancy of Onondaga (Effler et al ., ). Differences in fraction of inflow to the UML (Path B) were also predicted for these days and the two tributaries.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The predicted inflow centroid depths in spring (Figure a) were deeper, when lake stratification was relatively weak. Moreover, the predicted centroid depth was somewhat deeper on these three days for Onondaga Creek compared to Ninemile Creek, consistent with the usually greater negative buoyancy of Onondaga (Effler et al ., ). Differences in fraction of inflow to the UML (Path B) were also predicted for these days and the two tributaries.…”
Section: Resultsmentioning
confidence: 97%
“…Onondaga and Ninemile Creeks (Figure ) are the largest tributaries to the lake, with nearly equal size watersheds (~300 km 2 ), annual contributions to total inflow (~30%) (Effler, ), and similar loading rates for bioavailable forms of P (Effler et al ., ). Both streams are unusually saline, making noteworthy contributions to their negative buoyancies (Effler et al ., ). Natural groundwater seepage of sodium chloride brine occurs in Onondaga Creek (Owens et al ., ), while the salinity ( S , ‰) of Ninemile Creek is mostly residual waste from soda ash manufacturing (Effler and Matthews, ).…”
Section: Study Systemmentioning
confidence: 97%
See 2 more Smart Citations
“…The results from this study suggest one should characterize dissolved P according to its uptake kinetics instead of operationally classifying P fractions merely based on wet chemistry analyses (Hudson et al, 2000;Rigler, 1968). Also, recent research has shown that particulate P (PP) in municipal effluents may have a lesser contribution to effective P loading due to sediment deposition (Effler et al, 2009(Effler et al, , 2012. The assumption that the mineralization of particulate P is similar to dissolved P is also problematic.…”
Section: Implication For Watershed Managementmentioning
confidence: 95%